Research and implementation of a highly reliable transient and same source data comparison method based on fault recorder documents. Issue 1 (1st April 2022) - Ma, Huan; Xu, Yao; Xu, Chanpeng; Zhang, Dongxian; Mu, Yunlong; Zhang, Hao; Han, Minchou
Abstract: The existing fault recording analysis system has powerful functions in the analysis of fault characteristic factors such as waveform analysis, vector analysis, and harmonic analysis. However, it uses redundant fault recording data to analyze, compare and locate faults in the power system. Rarely involved, far from reaching the level it should be, and even wasting fault recording data with large amounts of data and rich information content. A highly reliable transient homology data comparison based on recording files is given. Analytical method. Introduced the comparison method of the recording data from the same source, the content involves how to match the channel waveform of fault recorder documents, how to use the zero-crossing algorithm to align, how to find the starting point of the protection action through the mutation amount algorithm, and how to pass the cubic spline The interpolation algorithm obtains valid data, how to compare the valid data, and finally obtain the comparison result, and give advice on operation and maintenance.